Pengaruh variasi laju aliran fluida terhadap kapasitas pengeringan pakaian (tipe pengering lemari) - Syamsuri Syamsuri; Zain Lillahulhaq; Akhfaruhal Akhfaruhal (Universitas Muhammadiyah Metro, 2023)
Clothes dryers are now widely used to help with laundry. During the rainy season, drying clothes outside is impractical. Furthermore, clothing may become contaminated with pollution. The rotating drum dryer is the most widely used model for utilizing centrifugal force. However, there are some disadvantages, such as wrinkled clothes from sun drying. The purpose of this study was to determine heat transfer in a clothes dryer with a drying cabinet type. The clothes to be dried are hung on a rack and blown dry with hot air. Convection will reduce the amount of water in the clothes. The hot air inlet velocity was varied between 3m/s, 4m/s, and 5m/s for this study. Changes in clothing surface temperature, calorific value, and efficiency were measured. The findings indicated that the air entering the drying cabinet must be moving at a slow speed. As a result, the incoming air has more time to transfer heat and contains more energy.